The The Effect of Inquiry-Based Learning on Secondary Student Learning Outcomes in Writing Ability - Sitti Maryam Hamid; Andi Bulkis Maghfirah Mannong; Nur Hidayat; Lilih Insyirah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
Inquiry-Based Learning is one of the teaching approach that requires students to actively construct and develop their ideas. It gives students meaningful experiences and insights in constructing their ideas in a coherent and structured manner. A pre-experimental research design using quantitative approach with one-group pre-test post-test design was implemented. Research questions was addressed: what is the effect of Inquiry-Based Learning on the students’ learning outcomes in writing ability? The sample of this study was thirty-students in 11th grade of SMA Muhammadiyah 5 Makassar. Students were given a pre-test and post-test which were analyzed to determine students’ learning outcomes in writing descriptive text. Upon testing the hypotheses, the results indicated that there was significant difference between students’ learning outcomes in pretest and post-test after Inquiry-Based Learning was implemented. The writers proposed that Inquiry-Based Learning be implemented in other English skills, higher education levels, and for both normal and special needs students.